The Interdisciplinary Character of Research into the Translation of Literary Irony - De Wilde, July (TTR)

(untitled) (Association canadienne de traductologie, 2012)
In this article, while I welcome the call for a more interdisciplinary character, I also endorse the idea that the methods of neighbouring disciplines do not necessarily need to be included into one comprehensive research model for TS. The advantages of interdisciplinary research are illustrated with research into the translation of literary irony. In the first part of the article, I present an analytical instrument for comparative research between original and translated ironic excerpts. I will demonstrate that by including insights from, mainly, pragmatic and cognitive approaches to irony, I have been able to fine-tune the three-part analytical instrument called “the ironic effect.” Its advantages and heuristic scope are illustrated with excerpts from La tía Julia y el escribidor (Mario Vargas Llosa). In the second part of the article, I discuss the analyses of two other novels, Tres tristes tigres (Guillermo Cabrera Infante) and La invención de Morel (Adolfo Bioy Casares) and show that, by adopting very different research hypotheses and multiplying the questions asked, the observed data were better understood. I conclude that there is margin for an inclusive, open and flexible TS methodology, provided that both theory and methodology are understood as means of understanding. Stripped of its ontological status, theory, then, is nothing but a functional notion.